Problems and prospects of codification of environmental legislation in the Russian Federation and in the Republic of Belarus within the framework of the Union State - Ponomarev, Mikhail V. (Journal of the Belarusian State University. Law, 2023)
The article examines the main trends, problems and perspectives of the systematisation of environmental legislation in the form of the environmental code. For that purpose, the experience of codification of environmental legislation in some countries of Western Europe in the countries of post-Soviet area, as well as the possibility of using this experience during the work on the codification of environmental legislation in the Russian Federation and the Republic of Belarus is examined.